2019
DOI: 10.1139/apnm-2018-0379
|View full text |Cite
|
Sign up to set email alerts
|

Changes in arterial stiffness after eccentric versus concentric cycling

Abstract: This study compared changes in brachial-ankle pulse wave velocity (baPWV) after concentric (CON) versus eccentric (ECC) cycling. It was hypothesized that baPWV would increase after the first ECC bout (ECC1) because of muscle damage, but not after the second ECC bout (ECC2), and would decrease after CON. Fifteen young (aged 20–30 years) men performed 2 bouts of 30-min ECC (ECC1 and ECC2) at 60% of maximal CON power output and 2 bouts of 30-min CON at the same intensity as that of ECC (CON1), and at the same oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
1
1
Order By: Relevance
“…Therefore, despite the elevation in muscle damage and inflammatory biomarkers, there was not a deterioration of vascular health after a COD sprinting exercise. Comparing different modalities of eccentric-based exercise, studies have demonstrated an increase in arterial stiffness after downhill running [ 53 ] and no changes after eccentric cycling [ 54 ], which is contrary to the results of the current study. Moreover, a previous meta-analysis comparing resistance and endurance exercise demonstrated a greater increase in arterial stiffness after resistance exercise [ 55 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, despite the elevation in muscle damage and inflammatory biomarkers, there was not a deterioration of vascular health after a COD sprinting exercise. Comparing different modalities of eccentric-based exercise, studies have demonstrated an increase in arterial stiffness after downhill running [ 53 ] and no changes after eccentric cycling [ 54 ], which is contrary to the results of the current study. Moreover, a previous meta-analysis comparing resistance and endurance exercise demonstrated a greater increase in arterial stiffness after resistance exercise [ 55 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Acute exercise intervention can induce transient changes in arterial function and structure. With different exercise types and intensities, exercise may have different or even opposite effects on the arterial elastic function [ 20 ]. Higher arterial stiffness and elastic modulus mean worse arterial elastic function.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was determined using G*Power (version 3.1.9.7; Heinrich-Heine University, Düsseldorf, Germany). The primary endpoint under investigation was baPWV, and the potential variation in baPWV over time (Pre, Post30, Post60) among the three groups (TM, men, women) was calculated for statistical power using a two-way analysis of variance (ANOVA) with an estimated effect size of 0.25, α = 0.05, β = 0.8, consistent with previous studies (Okamoto et al, 2019). A minimum of 12 participants were included in the study in each group.…”
Section: Discussionmentioning
confidence: 99%
“…The participants rested supine in the room for 30 min, after which the brachial-ankle pulse wave velocity (baPWV), brachial BP and heart rate (HR) were measured (PWV/ABI form: Omron Colin Co., Kyoto, Japan). Using the baPWV method, BP measurement cuffs wrapped around both the upper arms and ankles were inflated at low pressure (50 mmHg), and measurements were made using a volume pulse wave (Okamoto et al, 2019). Taken as the result for the right upper arm.…”
Section: Experimental Protocolmentioning
confidence: 99%